MOBILE PHONES AS USEFUL LANGUAGE LEARNING TOOLS - El Hariry, Nashwa Ahmed (European Scientific Journal, ESJ, 2015)
Most youth are passionate about having the most recent mobile phones just to boast among their peers. They use them to make phone calls, take photos, listen to songs, watch videos, or gain access to the internet for entertainment. This paper presents how to change the mobile phone device from a communication device to an educational tool. It demonstrates that a mobile phone could be a useful tool in learning and teaching the English Language. In this paper, the researcher emphasize the potential of mobile phones as a learning tool for students and have incorporated them into the learning environment. The paper discusses the challenges and expected difficulties. Many theories(e.g. Behaviourist learning, Constructivist learning, Situated learning, Sociocultural theory of learning, Informal and lifelong learning) relevant to the use of mobile phones in education are presented and the different tasks and activities relevant to them are explored. The salient features of mobile phones which make them useful for language learning are discussed too. The possible methods that should be used for gaining the best of learning through mobile phones are proposed. Activities are classified in terms of the main theories and areas of learning relevant to learning with mobile technologies. This article concludes with a discussion of how moderate use of mobile phones may bring interest among the learners and transform the learning process as it helps learners to raise their self – esteem and self- confidence. The researcher tries to foresee the future of mobile learning in general and mobile phones in particular in learning English since the English language has become the most requested and widespread means of communication all over the world.